The Distribution and Influence Factors of Non-Invasive Tear Film Break-Up Time in Children - Zhao GH; Wang JD; Liu MR; Zhang LJ; Sun Y; Cao K (Clinical Ophthalmology, 2024)
Guo-Hong Zhao,1 Jin-Da Wang,1 Mei-Rui Liu,2,3 Li-Jun Zhang,4 Yan Sun,5 Kai Cao6 1Beijing Tongren Eye Center, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of China; 2Department of Pulmonary Rehabilitation, Emergency General Hospital, Beijing, People’s Republic of China; 3School of Public Health, North China University of Science and Technology, Tangshan, Hebei, People’s Republic of China; 4Department of Obstetrics and Gynecology, Linyi Hospital of Traditional Chinese Medicine, Linyi, Shandong, People’s Republic of China; 5Department of Ophthalmology, Linyi Hospital of Traditional Chinese Medicine, Linyi, Shandong, People’s Republic of China; 6Beijing Institute of Ophthalmology, Beijing Tongren Hospital, Capital Medical University, Beijing, People’s Republic of ChinaCorrespondence: Kai Cao, Email crcteam@163.comObjective: To explore the distribution and influence factors of non-invasive tear film break-up time (NIBUT) in children.Methods: This is a hospital-based cross-sectional study. Spherical equivalent error (SER) was measured with cycloplegia. NIBUT was measured by an ocular surface integrated analyzer.Results: A total of 1269 children (1269 eyes) were included in this study. Participants’ median age was 11 (range 6– 18) years. 47.1% (598/1269) of participants were boys. The median NIBUT of myopic children and non-myopic children were 9.9 seconds (s) (Inter-quartile range, IQR: 6.4 to 16.1) and 10.9 s (IQR: 8.8 to 17.9), respectively, which was statistically significant (p = 0.004). In myopic children, 49.9% (573/1148) were able to achieve NIBUT of 10 s or more, compared to 67.8% (82/121) in non-myopic children, which was statistically significant (p < 0.001). There were 41 (3.57%) children in the myopic group and none (0%) in the non-myopic group with dry eye disease (p = 0.028). There was a positive correlation between NIBUT and age: NIBUT = 9.256 + 0.352*Age. 71.8% (824/1148) of myopic children used electronic products almost every day, compared to 37.2% (45/121) of non-myopic children, which was statistically significant (p < 0.001).Conclusion: The NIBUT of myopic children was significantly shorter than that of non-myopic children. Children with myopia are more likely to have dry eyes. NIBUT increases with age. High frequency of electronic product use may be an important cause to NIBUT shortening in children.Keywords: Tear film break-up time, dry eye, Myopia, ocular surface, children